Geological Analysis of the Influence of the Euphrates and Shatt al-Arab Rivers on Soil Texture and Density in Northern Basra, Southern Iraq - Najed F. Shareef (University of Thi-Qar Journal of agricultural research, 2025)
The study aimed to analyze the contrasting geological influences of the Euphrates River and the Shatt al-Arab on the physical properties of the soils in northern Basra. The methodology relied on collecting 18 surface samples from six sites (S1–S6) along both rivers, with a calculated distance from each. A particle size analysis of the soil texture was conducted following Folk’s method (1974). Bulk density, particle density, and total porosity were measured and supported by statistical analyses to examine the relationship between these properties and the distance from each river. The results revealed a dominance of fine particles (clay and silt) in the soil texture, reflecting a low energy depositional environment. Statistical correlations indicated two fundamentally different influence patterns. The Euphrates River exhibited a regular and gradual effect, showing a strong negative correlation (r = –0.797) between sand content and distance from the river, as well as a positive correlation for bulk density (r = 0.513) and a negative correlation for porosity (r = –0.495) with increasing distance. This pattern suggests the role of conventional hydraulic processes in grain size sorting. In contrast, the influence of the Shatt al-Arab appeared more complex and nonlinear, dominated by strong correlations associated with fine particles. Clay showed a strong negative correlation (r = –0.840), while silt exhibited a positive correlation (r = 0.729) with increasing distance from the river. This pattern may be attributed to tidal effects that enhance selective clay deposition near the riverbanks over long time periods. Moreover, particle density displayed notable stability, with no significant correlation with either river, indicating a homogeneous mineral source of the soils. The study concludes that the geological influence of the two rivers is integrated yet somewhat complex: The Euphrates controls the spatial distribution of coarse particles and soil porosity structure, whereas the Shatt al-Arab dominates the dynamics of fine particle distribution, collectively shaping the distinctive depositional patterns of the stratigraphic record within the floodplain of the study area.